Analisa Human Error Menggunakan Metode Systematic Human Error Reduction and Prediction Approach (SHERPA) Dan Human error Assessment and Reduction Technique (HEART) Pada Pengujian Destructive Test Mesin Milling Studi Kasus PT ABCD - Dinda Okta Dwiyanti Ridwan Gucci; Ricky Abdul (JURNAL REKAYASA SISTEM INDUSTRI, 2023)
PT ABCD is a company engaged in ship classification by means of testing or inspection, one of the inspections carried out is the Destructive Test (DT) where testing is carried out by applying pressure to the material using a milling machine, with a maximum limit value output. and minimum on the samples that have been tested. In the testing process, there are interactions that occur between humans and machines and each activity will tend to experience errors in the form of system errors or human errors. Therefore, conditions caused by human error must be minimized by making repairs so that work accidents and errors do not occur, because this will cause losses for the operator and the company later. The method used in this study is the SHERPA and HEART methods. The purpose of using the SHERPA method is to reduce errors and provide specific solutions from the analysis of the data that has been collected. Human Errors that occur are carried out on the awareness of machine operators, this is due to operators who work in a hurry and lack of time. The solution to overcome the Human Error that occurs is that there must be firmness from the Operation Manager and the Head of the Coordinator of the Destructive Test Laboratory (DT), such as re-checking the results of the operator's work, then before working it is expected to conduct briefing first to always remind to work according to applicable procedures, and lastly provide OHS training to all operators to better understand and realize the importance of implementing OHS in every work activity.